Pemanfaatan Ekstrak Daun Kecubung (Datura metel L.) Sebagai Pembius Ikan Koi (Cyprinus carpio L.) Pada Saat Pengangkutan - Sapto Eko Hariyanto; F. Sinung Pranata; Yuniarti Aida (Universitas Atma Jaya Yogyakarta, 2008)
Either decorative fish or consumption fish would be costlier in price if sold in a state of life. However both having the same problems that is death at the time of transportation process. From former research has been obtained information that transportation of fish in a state of life can be done by using material anaesthesia either experiencing and also artificial. Usage of chemical material as fish anaesthetic is felt able to give unfavourable effect to quality and fish health. Purpose of this research knows concentration of metel thorn apple leaf extract and soaking stripper that is most effective in anaesthesia of fish koi (Cyprinus carpio L.) and knows does metel thorn apple leaf extract can lessen fish mortality koi (Cyprinus carpio L.) at the time of transportation of long distance. Initial concentration which will be applied is 0,4%, 0,1%, 0,06%, 0,03% and 0% as control, because concentration doesn't have an effect on concentration is boosted up to become 0,4%, 0,7% and 1% with soaking stripper 4, 8, 12 hours. Result of research shows concentration of 0,7% and soaking stripper of 8 hour, this time is most effective in anaesthesia of fish koi (Cyprinus carpio L.) because level of survival rate 100% with induction time stripper and recovery time is stripper. Research is continued with test trasportasi compared to control, where fish is not anaesthetized packed into plastic poke and given with pure oxygen like treatment that is usualy is done the fish farmers in process of transportation. Result of this research indicates that, treatment of fish anaesthetized with metel thorn apple leaf extract level of pass of life reachs 91,667% while controlling 66,667%. From result of inferential research that usage of metel thorn apple leaf extract at the time of transportation of proven long distance can lessen fish mortality koi (Cyprinus carpio L.).